Are the needs of people with mental health problems met? - Tseliou, Foteini; Rosato, Michael; O'Reilly, Dermot (International Journal of Population Data Science, 2018)
Background High levels of mental ill-health have resulted in increasing delays in the receipt of appropriate care. However, the size of the gap between mental health needs and the likelihood of receiving treatment has not been thoroughly investigated on a population-level within Northern Ireland. Objectives To that end we investigated the link between self-reported mental ill-health and likelihood of being in receipt of treatment in a population cohort. Methods The 2011 Northern Ireland Census was linked to a population-wide prescribing database. The presence of a chronic mental health condition, as assessed through the Census self-reported mental health question, was compared to regular psychotropic medication use in the six and twelve months following the Census. Of the 23,803 individuals (aged 25 to 74) who reported chronic mental ill-health at the Census, 22% were not in receipt of medication over the following six months, with this being reduced down to 18.5% by the twelve month mark. Findings After adjusting logistic regression models for socio-demographic factors, men (OR=0.56: 95%CI=0.52-0.60), those of non-white ethnicity (OR=0.38: 95%CI=0.26-0.54), never married (OR=0.67: 95%CI=0.61-0.82), unemployed (OR=0.65: 95%CI=0.53-0.81) and living in a rural area (OR=0.88: 95%CI=0.79-0.98) were less likely to receive regular medication, indicating mental health unmet need. Conclusions A level of discord was observed between mental-ill health and medication receipt on a population level. Further focus on mental health needs and the impact of low prescribing rates on mental health patients could help ameliorate the current inequalities and reduce potential gaps in mental health treatment.